Pengaruh Faktor Relatif dan Kontekstual Terhadap Perilaku Pembelian Konsumen dengan Religiusitas Sebagai Variabel Mediasi (Studi Kasus Fashion Busana Muslim di Semarang) - Aprillia Elly Kusumastuti; Rizqi Ayu Kumalasari (EBBANK, 2017)
Lifestyle changes and the progress of time has raised Muslim fashion becomes the trend in the society. However, over the more modern era there has been a shift in the meaning of the use of Muslim dress for Muslim women. This is because the influence of modernization where Muslim clothes is not a primary goal but made a new fashion trend among the community. It was a debate in society whether a Muslim veil because of the demands of their religion or mere fashion trend. This study aimed to test whether the relative and contextual factors influence the behavior of muslim consumers with religiosity as the mediating variable. The population in this study were all Muslim consumers who use the Muslim fashion in the city of Semarang.. The number of samples in this study were 100 respondents with a acidental sampling techniques. This study uses analysis techniques path (path analysis). Based on the results of hypothesis testing is known that the relative and contextual factors influence consumer buying behavior, Relative and contextual factors influence the religiosity. Religiosity influence on consumer buying behavio. and Religiosity is a mediating variable between relative and contextual factors on consumer buying behavior.